Development of a front-end electronics for thin-gap resistive plate chamber. (4th November 2021) - Ge, J.J.; Li, Q.Y.; Su, C.; Xue, Z.W.; Liu, Y.W.; Sun, Y.J.; Liang, H.
Abstract: To cope with the challenge of high hit rates in some applications, the new-generation large-area Resistive Plate Chamber (RPC) with 1 mm thin gap was proposed. Compared to the RPC generation presently, the signal of the thin-gap RPC is much weaker (of the order of hundreds of μV) and faster (pulse width of about 5 ns). Hence a new-generation Front-End (FE) electronics needs to be developed for the thin-gap RPC. The FE board contains 8 independent electronic channels, each with an amplifier, a discriminator, and a Low-Voltage Differential Signaling (LVDS) transmitter. The amplifier is made of discrete components, with particular emphasis on SiGe:C transistors. A simplified but stable power system is designed for the FE board, and its status can be monitored in real-time. The test results show that the overall charge gain of the FE amplifier reaches 0.4 mV/fC, with very low noise (lower than 700 μV RMS with up to 10 pF input detector capacitance), and good linearity when the amplitude of the input amplitude is lower than 3 mV. The -3-dB bandwidth of the amplifier reaches 154 MHz. The jitter caused by the electronics (including amplifier, discriminator and LVDS transmitter) is around 10 ps when the threshold voltage is higher than 20 mV. The maximum event rate per channel exceeds 20 MHz. The cosmic ray test was conducted with two FE boards mounted on a 1 mm thin-gap RPC of 1.4 × 0.4 m 2 area. The efficiency of the detector system reaches 95% when the threshold voltage is 20 mV, with almost no accidental coincidence event. The overall time resolution of the detector system is 484 ps. The performance of our FE electronics satisfies the requirement of the thin-gap RPC.